1997
DOI: 10.1038/bjc.1997.203
|View full text |Cite
|
Sign up to set email alerts
|

Spatial association of apoptosis-related gene expression and cellular death in clinical neuroblastoma

Abstract: Summary Several unique features of neuroblastoma (NB), including the capacity for spontaneous regression and maturation to benign pathology, suggest that genes that regulate cellular proliferation, survival and differentiation may be involved in directing clinical tumour aggressiveness. The in situ expression of Bcl-2, Rb, p21, p53 and Bax proteins, as well as the proliferation marker proliferating cell nuclear antigen (PCNA) were examined immunocytochemically in a selection of 38 stage-and outcome-identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 57 publications
2
36
0
Order By: Relevance
“…Depending on the differentiation stage of the tumor cells at diagnosis, the clinical behavior can be predicted, with immature tumors being more aggressive and having a poor prognosis (16,17). Neuroblastoma derives from immature sympathetic neural precursors, often with remaining neural crest traits (14,15,18). We have previously found that hypoxic neuroblastoma tumors and cells exposed to hypoxia (1% O 2 ) down-regulate SNS marker genes, including the * This work was supported by grants from the Swedish Cancer Society, the Children's Cancer Foundation of Sweden, Åke Wiberg's Foundation, HKH Kronprinsessan Lovisas förening för barnasjukvård, Hans von Kantzow's Foundation, Ollie and Elof Ericsson's foundation, the Crafoord Foundation, and Malmö University Hospital Research Funds.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the differentiation stage of the tumor cells at diagnosis, the clinical behavior can be predicted, with immature tumors being more aggressive and having a poor prognosis (16,17). Neuroblastoma derives from immature sympathetic neural precursors, often with remaining neural crest traits (14,15,18). We have previously found that hypoxic neuroblastoma tumors and cells exposed to hypoxia (1% O 2 ) down-regulate SNS marker genes, including the * This work was supported by grants from the Swedish Cancer Society, the Children's Cancer Foundation of Sweden, Åke Wiberg's Foundation, HKH Kronprinsessan Lovisas förening för barnasjukvård, Hans von Kantzow's Foundation, Ollie and Elof Ericsson's foundation, the Crafoord Foundation, and Malmö University Hospital Research Funds.…”
mentioning
confidence: 99%
“…Neuroblastoma (NB), the most common extracranial solid pediatric tumor, arises where sympathetic nervous system (SNS) tissue forms (14,15). Depending on the differentiation stage of the tumor cells at diagnosis, the clinical behavior can be predicted, with immature tumors being more aggressive and having a poor prognosis (16,17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These data, obtained in two independent laboratories, challenge the previously proposed ID2-MYCN relation. Oncogene (2003Oncogene ( ) 22, 456-460. doi:10.1038 Keywords: ID2; MYC; MYCN; neuroblastoma; prognosis Neuroblastoma is a childhood tumor derived from sympathetic nervous system precursor cells (Hoehner et al, 1996(Hoehner et al, , 1998. Detailed cytogenetic characterization indicates that neuroblastoma can be divided into subgroups based on their genetic aberrations, but the molecular events leading to malignant transformation of these neural crest-derived precursor cells are not known in any detail.…”
mentioning
confidence: 99%
“…4 ± 7 Apoptosis also takes place within the primary neuroblastoma as the tumour cells move away from the fibrovascular stroma. 8 Positive correlations have been observed between frequency of apoptotic cells and favourable outcome of patient. 9 The mechanism behind the spontaneous regression of neuroblastoma is unknown, but one hypothesis suggests it was due to apoptosis.…”
Section: Introductionmentioning
confidence: 99%